Relationships between morphological features and physical performance depend on sex and age groups: a cross-sectional study among Brazilian beach volleyball players - Pontes, N. E.; Oliveira, L. S.; Batista, G. R. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND Understanding the evolution of morphological features and their relationship with physical performance may assist coaches and institutions in developing the next generation of beach volleyball (BV) athletes for senior-level competition. Thus, this study analyzed the morphological features of Brazilian BV athletes by sex among age groups, and their relationship with physical performance.